The Kyai’s Strategy to Develop Cadres with Islamic Characters - Iman, Nurul; Ikhwan, Afiful; Fadilah, Nur Hidayatul (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2023)
This article aims to explain the Islamic character regeneration model in Islamic boarding schools and the strategy of the kyai as the highest leader in developing Islamic character regeneration for students. The location of this research, namely Arrisalah Modern Islamic Boarding School Ponorogo, is unique from other sites because of the curriculum or general subjects at the Islamic boarding school, which is famous for its salaf curriculum, which is integrated with Islamic values typical of Islamic boarding schools. This study uses an interpretive paradigm through a qualitative approach, a case study type. The primary data were obtained from caregivers, madrasa heads, teachers, students, and other parties involved, using data collection techniques such as in-depth interviews, observation, and documentation. The analysis technique used is the Miles and Huberman data reduction models, data display, and verification. Checking data validity using triangulation: credibility, transferability, dependability, and confirmability. The study results show that the cadre model at Arrisalah Modern Islamic Boarding School is a reduction or transfer of the Islamic boarding school's Islamic character and values. The kyai's strategy in creating cadres with Islamic character is actualized in several aspects, including the kyai's example, curriculum, 'Ala Manhaj Rabbaniy education system, organization, Pondok discipline, and compulsory service. So, this research provides a lot of valuable insights into the cadre model in Islamic boarding schools, and it cannot be denied that there are still various opportunities for more in-depth and broad future research.